Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-8 Factoring by Grouping - Practice and Problem-Solving Exercises - Page 519: 17



Work Step by Step

$8m^{3}=$$2.2.2.m.m.m$ and $12m^{2}=2.2.3.m.m$ Hence, $GCF=$$2.2.m.m=$$4m^{2}$ After Grouping : $=(8m^{3}+12m^{2})-(2m+3)$ $=4m^{2}(2m+3)-1(2m+3)$ $=(4m^{2}-1)(2m+3)$ This can be further written as : $(2m+1)(2m-1)(2m+3)$ (since $(a^{2}-b^{2})=(a+b)(a-b)$)
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.